2021
DOI: 10.3390/jpm11100992
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Implementation of Personal Breast Cancer Risk Assessments

Abstract: Personal Breast Cancer (BC) Risk Assessments (PBCRA) have potential to stratify women into clinically-actionable BC risk categories. As this could involve population-wide genomic testing, women’s attitudes to PBCRA and views on acceptable implementation platforms must be considered to ensure optimal population participation. We explored these issues with 31 women with different BC risk profiles through semi-structured focus group discussions or interviews. Inductive thematic coding of transcripts was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…Our study revealed that receiving news of being at high risk of breast cancer may catch people off guard—some women felt that it may be better for them not to know their personal risk. Knowing one is at high risk but not knowing when or if breast cancer will develop may result in negative emotions associated with fear, powerlessness, and the belief that there is no escaping the disease, which may negate the benefits of risk-stratification [ 29 ]. Discussing breast cancer risk with at-risk women and promoting risk reduction techniques may thus cause anxiety and breast cancer worry [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that receiving news of being at high risk of breast cancer may catch people off guard—some women felt that it may be better for them not to know their personal risk. Knowing one is at high risk but not knowing when or if breast cancer will develop may result in negative emotions associated with fear, powerlessness, and the belief that there is no escaping the disease, which may negate the benefits of risk-stratification [ 29 ]. Discussing breast cancer risk with at-risk women and promoting risk reduction techniques may thus cause anxiety and breast cancer worry [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Evans et al reported that in comparison to women not classified as high risk, women at high risk for breast cancer were substantially more likely to acknowledge their breast cancer risk is high and to adhere to routine screening [ 55 ]. Results from the Personal Breast Cancer (BC) Risk Assessments (PBCRA) study ( n = 31, semi-structured focus group discussions or interviews) showed that the majority of women appreciate the chance for a risk-based screening programme to guide enhanced disease monitoring, but they were reluctant in accepting decreased surveillance if estimated to be at low risk since they are comforted by routine screening [ 29 , 56 ]. This is at odds with our focus group results where most participants, when told to consider a scenario where they are classified as “low risk” of developing breast cancer, would feel complacent and reduce their mammography visits or stop them entirely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential acceptability of incorporating polygenic risk scores has been demonstrated in a recent study reporting 84% uptake of a primary care-based polygenic risk assessment for colorectal cancer [ 89 ]. Additionally, evidence suggests that a risk assessment endorsed and performed by a familiar individual or institution, such as general practice, may be more acceptable to women and that uptake may be improved by easier access [ 83 ].…”
Section: Programme/system Principlesmentioning
confidence: 99%
“…Additional inductive thematic analysis was performed through iterative reading and coding of the focus group transcripts (J.C.W.W., M.A.S., reviewed by L.K.). 27 Test specificity and sensitivity criteria levels represent the proportion of women whose polygenic risk could reclassify them as below or above average risk. 28 Elicitation of criteria weights through swing weighting The 8 criteria and criterion levels were incorporated into an MCDA questionnaire in the following manner.…”
Section: Design and Implementation Of The Mcda Surveymentioning
confidence: 99%